Rivalitas Cina dan Jepang dalam Institusi Regional Asia Timur - Veronica, Nuri Widiastuti (Global: Jurnal Politik Internasional, 2014)
East Asia has been widely known as the arena for geopolitical contestation between the great players and has been called as 'the grand chessboard' for geopolitical struggles, especially for the two regional powers, Japan and China. These two powers possess huge potentials to become the driving actors for the formation of regional mechanisms in East Asia, such as East Asian Community (EAC) dan China-ASEAN Free Trade Area. Economic cooperation between China and Japan in some regional forums brings hopes to end the long-term tensions and prospects for reconciliation among them. However, the interdependence between them does not simultaneously change the influence contestation and competition, especially for these past decades. This paper will try to answer a question about the form of competition between Japan and China in the context of regional institution in East Asia. By using theoretical approach of rivalry on interdependency, this paper try to analyze the roles of the two great powers in multilateral forums in East Asia, how those roles reflect their competition and what obstacles are heading their ways to be the "leader" in East Asia regional forums.